Analysen zur Leistungsentwicklung im Eiskunstlaufen bei den Olympischen Winterspielen 2018 - Weigmann-Faßbender, S.; Dunkel, K.; Knoll, Ka. (Leipziger Sportwissenschaftliche Beiträge, 2018)
In figure skating competition, performance is affected by the development of the judging system. On a regular basis, program contents or special guidelines for the evaluation of presented elements in short or free programs are changed. In the last four years there were some changes in the base values of selected elements e.g. jumps, throw jumps or lifts, but not in the program content. In general, compared to the Olympic Winter Games 2014, we identified performance improvements in all four figure skating events. Especially quadruple jumps in the men`s competition and a very high degree of difficulties and outstanding presentations in pairs´ and ladies´ competitions could be identified as essential for these improvements.